Temporary Epicardial Pacemaker Wires: Significance of Position and Electrode Type - Aser, Raed; Orhan, Coskun; Niemann, Bernd; Roth, Peter; Perepelitsa, Andre; Attmann, Tim; Böning, Andreas (The Thoracic and Cardiovascular Surgeon, 2014)
Objective To determine the pacing and sensing properties of different temporary epicardial pacemaker electrodes after cardiac surgery depending on position at the heart and time after surgery.Methods From September 2009 to October 2010, 60 patients undergoing cardiac surgery were prospectively randomized into two groups: group O: Osypka-electrodes (n = 30), group M: Medtronic-electrodes (n = 30). In position 1, the bipolar electrodes were inserted onto the anterior wall of the right ventricle and at the right atrial auricle, in position 2, onto the diaphragmal wall of the right ventricle and at the aortic aspect of the superior vena cava medial close to the atrium. Sensing values and pacing thresholds were measured for all electrodes during surgery, on day 1 and every second day up to day 10 after surgery.Results In both groups, pacing thresholds (both positions) were higher during surgery (ventricle 3.1 ± 0.6 V, atrium 3.1 ± 0.3 V) than at day 1 (ventricle 2.4 ± 0.7 V, atrium 2.4 ± 0.3 V) and increased during the perioperative course until day 10 (ventricle 4.7 ± 1.0 V, atrium 4.9 ± 1.1 V, p = 0.04, p = 0.02). P and R wave amplitudes did not change over time (atrium 5.1 ± 0.1 mV initially, 4.2 ± 0.1 mV at removal (p = ns); ventricle 10.4 ± 0.2 mV vs. 10.1 ± 0.25 mV). Group M had better median pacing thresholds compared with group O (atrium: 2.9 ± 0.6 V vs. 3.9 ± 0.7 V, p = 0.04 and ventricle: 2.6 ± 0.6 V vs. 3.9 ± 0.6 V, p = 0.045). Atrial position 1 was superior to position 2 concerning pacing thresholds of Medtronic electrodes (2.1 ± 0.3 mV vs. 3.4 ± 0.4 mV, p = 0.02). Osypka-electrodes were easier to handle due to their more pliable texture.Conclusions 1. Up to postoperative day 10, adequate pacing and sensing performance was achieved by both electrode types in each position. 2. Medtronic electrodes had better pacing thresholds in atrium and ventricle after day 5. 3. Positioning of pacemaker electrodes does not alter functionality. 4. Handling of Osypka electrodes was easier than that of Medtronic electrodes.